2011
DOI: 10.5505/tjtes.2011.22800
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric head injuries, retrospective analysis of 851 patients: An epidemiological study

Abstract: AMAÇBu çalışmanın amacı, çocukluk çağı kafa travmaları konusunda ülkemizin epidemiyolojik verilerine katkıda bulunmaktır. GEREÇ VE YÖNTEM Ocak 2003 ile Haziran 2008 tarihleri arasında SamsunMehmet Aydın Eğitim ve Araştırma Hastanesi Nöroşirürji Kliniğinde yatarak tedavi edilen 0-14 yaşları arasında toplam 851 hasta geriye dönük olarak incelendi. BULGULARHastaların 550'si (%65) erkek, 301'i (%35) kadındı. Travma nedenleri arasında düşme (%70) ilk sırada yer alıyor-du. Giriş Glasgow Koma Skalasına (GKS) göre %74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
1
9
1
5
Order By: Relevance
“…However, operative interventions were required in 29 (17.3%) patients on account of open skull fractures and for evacuation of intracranial hematomas. This rate of surgical intervention is about the same as 10.5% reported by Işık et al [13] in an earlier study. Significant good outcome (138, 81%) reported in this study was similar to the findings by Nnadi et al [10] in Calabar (92.1%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, operative interventions were required in 29 (17.3%) patients on account of open skull fractures and for evacuation of intracranial hematomas. This rate of surgical intervention is about the same as 10.5% reported by Işık et al [13] in an earlier study. Significant good outcome (138, 81%) reported in this study was similar to the findings by Nnadi et al [10] in Calabar (92.1%).…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of mild TBI recorded in this study (79, 47.0%) [Table 4] is lesser than 60% and 74% as reported by Emejulu and Shokunbi[7] and Işık et al ,[13] respectively. Earlier study in Ilorin by Odebode and Abubakar,[14] which reported lower incidence of TBI (37.5%), was conducted at a time when neither CT scan nor neurosurgical service was available at our center to confirm and manage brain injury.…”
Section: Discussioncontrasting
confidence: 62%
“…En un metaanálisis del grupo IMPACT (del inglés International Mission on Prognosis and Analysis of Clinical Trials in TBI) describieron como causa principal el accidente automovilístico seguido por las caídas y los accidentes deportivos en pacientes mayores de 14 años (31) . Sin embargo, en otros lugares geográficos como África, Oriente medio y el sur de Asia se reportan las caídas como la principal causa del TCE, seguidas de accidentes de tránsito y trauma no accidental (5,(32)(33)(34) . Según Michael et al, estas variaciones demográficas pueden estar dadas por el nivel de desarrollo del país (14) .…”
Section: Discussionunclassified
“…Işık et al showed a 3.8% of mortality among head traumas in children 7 . Head trauma caused by fallen television causes greater mortality and morbidity than the other types of head traumas among children [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%